Interview with Elizabeth Closs Traugott and Graeme Trousdale - Karen Sampaio Braga Alonso; Diego Leite de Oliveira (Revista Linguística, 2023)
Since the last decade, many books and papers have been published in the field of Language Change, under a Functional-Cognitive approach. Among these contributions, the book Constructionalization and Constructional Change (Traugott Trousdale, 2013) became a must read to those who work or intent to work on constructions from a diachronic perspective. The authors, Elizabeth Traugott and Graeme Trousdale, brought out to the audience a thought-provoking book about how new constructions are coined in language throughout the centuries. For that, they establish a difference between constructionalization and constructional changes, considering the former as the creation of a new construction and the latter as changes in the form or in the meaning of an existing construction. In Brazil, and all over the world, the book gained popularity and figured in the center of a rich debate concerning the conciliation between construction grammar, a theoretical model about the speaker’s knowledge of language, and language change, which goes beyond the individual’s lifespan. For those who adopted the concepts of the book and or criticized some of the definitions and understandings presented by the authors, there are still several open questions regarding a diachronic approach to grammar. In the wake of this debate, we are very happy to have interviewed Elizabeth Traugott (Professor Emerita at Stanford University) and Graeme Trousdale (Professor at The University of Edinburgh) to celebrate ten years of the publication of Constructionalization and Language Change. In this interview, you will be able to follow the way the authors see the work of 2013, how they dialogue with the criticisms received and how they understand language change in 2023.